PENGARUH PROMOSI DAN KUALITAS PRODUK TERHADAP PENJUALAN RUMAH PADA PT. RAFINDO MUTIARA ABADI PEKANBARU - Diifa, Abdiasa Muhamad; Karneli, Okta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research was conducted at PT. Rafindo Mutiara Abadi Pekanbaru. The purpose of this study was to determine the effect of promotion and product quality on home sales at PT. Rafindo Mutiara Abadi. Promotion as a variable (X1), Product Quality as a variable (X2) and Seller as a variable (Y). The sample of this study was taken as many as 72 respondents from the population calculated using the Slovin formula. This study uses the Stratified Random Sampling method, while the leadership and employees function as facilitators who provide supporting data in this study. In this research the method used is descriptive and quantitative with the SPSS program, data collection techniques through interviews, observation and questionnaires. From the results of data analysis which includes validity, reliability, simple linear, multiple linear, determination, and significance tests with t (partial), F (simultaneous) tests. This research shows that promotion has a significant effect on sales. Both product quality has a significant effect on sales. All three promotions and product quality simultaneously affect sales.Â Â Kata Kunci: Promotion, Product Quality, Sales